"It Isn't in the Curriculum": World History Teachers' Views on U.S. Presidential Elections. Issue 3 (3rd May 2020) - Bronstein, Erin A.
Abstract: This study examines world history teachers' attitudes regarding teaching U.S. presidential elections. During interviews with nine teachers, participants emphasized that the competing demands of their classrooms negatively influenced their willingness to teach about the U.S. presidential elections generally, and the 2016 Election specifically. The participants reconsidered their stances on not teaching elections during the interviews but struggled to reconcile their role as world history teachers with their priorities as social studies more generally. While elections are part of the civics curriculum and can be easily associated with history courses, this study suggests that greater attention should be paid to how citizenship practices can be understood through world history classes to promote teaching about elections as part of the curriculum.